Nothing to See? Paying Attention in the Dark Environment - Tainio, Matti (The Nordic Journal of Aesthetics, 2023)
A cloudy November evening deep in an old forest. It is really dark, and I try to observe my environment. I discern the difference between the treetops and the dark sky and the snow-covered ground. Everything else is formless. My vision is quite useless, and the other senses are weak in these circumstances. Only the background hum is audible and most aromas are erased by the freezing temperature. In a winter outfit, all I can feel is the moving air on my face. Yet, this is not sensory deprivation, there are things to observe. What is it possible to discern when the visual stimulus is minimized? This article focuses on the aesthetic experience of darkness by analyzing a visit to a deep natural darkness and attempts to connect this distinct case to aesthetic theory. The emphasis is on the descriptive analysis of the challenges of seeing in the darkness.